2017
DOI: 10.1177/0898010117714665
|View full text |Cite
|
Sign up to set email alerts
|

Finding Paradise Within: How Spirituality Protects Palliative Care Clients and Caregivers From Depression

Abstract: The aims of this article are to explore the experience of depression among palliative care clients and caregivers, describe the strategies they use in coping with depression, and clarify the role of spirituality in preventing and/or overcoming depression. This article discusses an aspect of the findings of a larger doctoral study that explored the nature of spirituality and spiritual engagement from the viewpoint of individuals with life-limiting conditions and their caregivers. van Manen's phenomenology was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Caregivers also experience spiritual challenges related to the imminent death of a loved one (Choi et al, 2013;Spatuzzi et al, 2017;Tang, 2009). Spirituality offers a coping source for many end-of-life caregivers that provides comfort, prevents depression, offers a sense of meaning making, hope, and belonging, a relationship with the 'sacred', and the facilitation of closure during the grieving process (Lalani, Duggleby, & Olson, 2018;Lander & Graham-Pole, 2008;Paiva, Carvalho, Lucchetti, Barroso, & Paiva, 2015;Penman, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Caregivers also experience spiritual challenges related to the imminent death of a loved one (Choi et al, 2013;Spatuzzi et al, 2017;Tang, 2009). Spirituality offers a coping source for many end-of-life caregivers that provides comfort, prevents depression, offers a sense of meaning making, hope, and belonging, a relationship with the 'sacred', and the facilitation of closure during the grieving process (Lalani, Duggleby, & Olson, 2018;Lander & Graham-Pole, 2008;Paiva, Carvalho, Lucchetti, Barroso, & Paiva, 2015;Penman, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Most health care professionals recognize spirituality, as a central component in health and healing (Dossey, 2016, Penman, 2018. In a classic work on the professional and ethical implications of spirituality in nursing care, Wright (1998) asserted within the concept of holistic nursing care, spirituality is viewed as being interdependent and interrelated with the physical and social components of all other human dimensions and is therefore central to the delivery of holistic care.…”
mentioning
confidence: 99%
“…Over recent decades, research on spirituality in nursing and health care has increased globally (Beres, 2017; Clarke, 2013; Martins, Romeiro, & Caldeira, 2017; Milligan, 2011; Penman, 2018; Pesut & Reimer-Kirkham, 2009; Ross et al, 2018). The International Council of Nurses (2012), the American Nurses Association (2015), and the Nursing and Midwifery Council (2009, 2014) in the United Kingdom have recognized the importance of spirituality to good nursing practice.…”
mentioning
confidence: 99%
“…Defining spirituality for research purposes is complex, and for this reason, some authors have used religious observance as a surrogate for spirituality, especially in quantitative research (Koenig, King, & Carlson, 2012). Robust studies have demonstrated the importance of spirituality (sometimes expressed through religion) in helping patients regain hope, meaning, and purpose in the midst of illness (Burkhardt, 2007; D’Souza, 2007; Koenig et al, 2012; Penman, 2018). Growing evidence suggests that addressing spirituality improves comfort levels (emotionally and physically) and has a positive effect on patients’ responses to illness and treatments (Koenig et al, 2012).…”
mentioning
confidence: 99%